Effects of obstruent voicing on vowel F0: Implications for laryngeal realism - Kirby, James; Ladd, D. Robert (Yearbook of the Poznan Linguistic Meeting, 2018)
In this paper, we present data on obstruent-intrinsic F0 perturbations (CF0) in two [voice] languages, French and Italian. Voiceless obstruents in both languages are found to raise F0, while F0 following (pre)voiced obstruents patterns together with sonorants, similar to the voiceless unaspirated stops of [spread glottis] languages like German and English. The contextual stability of this cue implies that an active de-voicing gesture is common to languages of both the [voice] and [spread glottis] types, and undermines the idea that a strict binary dichotomy between true voicing and aspirating languages can be reliably inferred based on properties of the surface phonetics.